An exploratory study of the relationship between changes in emotion and cognitive processes and treatment outcome in borderline personality disorder - McMain, Shelley; Links, Paul S.; Guimond, Tim; Wnuk, Susan; Eynan, Rahel; Bergmans, Yvonne; Warwar, Serine (American Economic Review, 2013)
This exploratory study examined specific emotion processes and cognitive problem-solving processes in individuals with borderline personality disorder (BPD), and assessed the relationship of these changes to treatment outcome. Emotion and cognitive problem-solving processes were assessed using the Toronto Alexithymia Scale, the Linguistic Inquiry Word Count, the Derogatis Affect Balance Scale, and the Problem Solving Inventory. Participants who showed greater improvements in affect balance, problem solving, and the ability to identify and describe emotions showed greater improvements on treatment outcome, with affect balance remaining statistically significant under the most conservative conditions. The results provide preliminary evidence to support the theory that specific improvements in emotion and cognitive processes are associated with positive treatment outcomes (symptom distress, interpersonal functioning) in BPD. The implications for treatment are discussed.